PENGEMBANGAN IDENTIFIKASI MULTIPLE INTELLIGENCE ( HOWARD GARDNER) BERBASIS APLIKASI ANDROID DALAM PENENTUAN PUTUSAN KARIR MAHASISWA DI YOGYAKARTA. - Ari Prasetyoaji; Widi Fajar Widyatmoko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2021)
Technology in this era, especially during pandemic, has become something important in supporting self-improvement activities. Online learning and mobile applications become more practical to use to help optimize individual self. This research has developed an application product to assist students in determining their career decisions through multiple intelligence detection initiated by Howard Gardner. The application that has been develop consists of 3 menus, namely 1) multiple intelligence by Howard Gardner, 2) intelligence test (Howard Gardner), and 3 ) education about multiple intelligences. Howard Gardner stated that every child has more than one potential intelligence that may be able to develop and the development of intelligence may differ from one person to another. The purpose of developing this application is to make it easier for students in Yogyakarta in making career decisions so that they are in accordance with the abilities, intelligence that exist within themselves. This research was developed using the Borg & Gall R&D research method.